Pulmonary Embolism in Hospitalized Patient with Coronavirus Disease 2019 (COVID-19) - Wulyo Rajabto; Dimas Priantono; Rahmad Mulyadi (Interna Publishing, 2022)
Coronavirus disease 2019 (COVID-19) has been a global pandemic for over a year. Meanwhile, thrombosis occurs in up to one-third of hospitalized patients with the disease, while pulmonary embolism has been reported to be the most dangerous thrombosis which greatly increases mortality in COVID-19. Hospitalized patients with COVID-19 are at high risk of thromboembolic complications such as deep vein thrombosis and pulmonary embolism. The hypercoagulable state caused by COVID-19 leads to activation of coagulation cascade, meanwhile, CT pulmonary angiography is used to diagnose or exclude pulmonary embolism. Furthermore, ground-glass opacities are also evaluated using this modality. Low molecular weight heparin is the anticoagulant of choice due to simplicity in administration and low risk of drug-drug interactions. Pulmonary embolism occurs in COVID-19 patients without DVT. Based on the results, parenteral anticoagulant followed by DOAC is the mainstay of treatment in COVID-19 coagulopathy.